Problems of women's education in Turkestan in the 19th century - Zebuniso Akhrorova (International Journal of Advanced Science and Technology, 2020)
This paper makes analyses of the problems of women's education in Turkestan in the 19th century. On this case, research has accentuated on Turkestan, and investigations were followed in the comparisons of 19th century. Finally it has concluded with the vivid analyses of the women's education in Turkestan in the 19th century.